2010
DOI: 10.3390/ijms11103705
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling Studies of 4,5-Dihydro-1H-pyrazolo[4,3-h] quinazoline Derivatives as Potent CDK2/Cyclin A Inhibitors Using 3D-QSAR and Docking

Abstract: CDK2/cyclin A has appeared as an attractive drug targets over the years with diverse therapeutic potentials. A computational strategy based on comparative molecular fields analysis (CoMFA) and comparative molecular similarity indices analysis (CoMSIA) followed by molecular docking studies were performed on a series of 4,5-dihydro-1H-pyrazolo[4,3-h]quinazoline derivatives as potent CDK2/cyclin A inhibitors. The CoMFA and CoMSIA models, using 38 molecules in the training set, gave r2cv values of 0.747 and 0.518 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In the CoMFA model, the contributions of the steric and electrostatic fields to activity were 40.9% and 59.1%. The yellow and blue contours located at the A site indicated that a bulky substituent would not be tolerated and electropositive groups would be favorable [22]. However, bulky substituents and electropositive groups would not be favorable to the B group (Figure 4a) [23].…”
Section: Resultsmentioning
confidence: 99%
“…In the CoMFA model, the contributions of the steric and electrostatic fields to activity were 40.9% and 59.1%. The yellow and blue contours located at the A site indicated that a bulky substituent would not be tolerated and electropositive groups would be favorable [22]. However, bulky substituents and electropositive groups would not be favorable to the B group (Figure 4a) [23].…”
Section: Resultsmentioning
confidence: 99%
“…The Surflex-Dock uses an empirical scoring function and a patented search engine to dock ligands into a protein’s binding site [18]. The scoring function considers the four terms, including the hydrophobic complementarity, polar complementarity, entropic terms and solvation terms.…”
Section: Methodsmentioning
confidence: 99%
“…The 3D structures of all compounds were constructed by using the Sketch Molecule module. Energy minimization of each structure was performed using the SYBYL energy minimizer Tripos force field and Gasteiger-Hückel charge [ 13 , 14 ]. Molecular alignment was considered as one of the most sensitive parameters in 3D-QSAR analysis [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this equation, SD is the sum of the squared deviations between the agonistic activities of the test set and the mean activity of the training molecules and PRESS is the sum of squared deviations between predicted and actual activity values for each molecule in the test set [ 13 , 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%